The complete mitochondrial genome of the hybrid of Schizothorax oconnori (♀) × Schizothorax waltoni (♂). Issue 1 (2nd January 2019) - Zhang, Chi; Zhou, Jianshe; Liu, Fei; Mou, Zhenbo; Chen, Meiqun
Abstract: Using Illumina next-generation sequencing (NGS), the complete mitochondrial genome sequence of the hybrid species of Schizothorax oconnori (♀) × Schizothorax waltoni (♂) was described in this study. 16, 592bp long circular molecule consisted of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and a control region. This study discovered the 99.8% sequence identity between the hybrid and its female parent, which confirmed the maternal inheritance pattern followed. The phylogenetic tree showed the hybrid was closer relationships with Schizothorax oconnori . The results would be a useful basis for conservation and phylogenetics of this hybrid.